2019
DOI: 10.1038/s41419-019-1813-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluoxetine on astrocyte autophagy flux and injured mitochondria clearance in a mouse model of depression

Abstract: Although multiple hypotheses had been proposed to clarify the causes of depression, the accurate pathogenesis and effective treatment of depression still need to be solved. Pathological change of astrocytes has been recognized to play a pivotal role in depression. Fluoxetine is the first selective serotonin reuptake inhibitor, however, the underlying mechanisms of fluoxetine are incompletely excavated. Emerging evidence shows that fluoxetine promotes autophagic processes in tumor cells. However, whether astroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 42 publications
3
92
0
Order By: Relevance
“…In the past few decades, most of the anti-MDD targets are considered to act on neurons such as monoaminergic, glutamatergic or GABAergic neurons, although recently growing bodies of studies reveal astrocytic responses to antidepressants (Cui et al, 2018;Shu et al, 2019). In the present study, we demonstrated Sig-1R can directly act on astrocyte to elicit antidepressant activity.…”
Section: Discussionsupporting
confidence: 51%
“…In the past few decades, most of the anti-MDD targets are considered to act on neurons such as monoaminergic, glutamatergic or GABAergic neurons, although recently growing bodies of studies reveal astrocytic responses to antidepressants (Cui et al, 2018;Shu et al, 2019). In the present study, we demonstrated Sig-1R can directly act on astrocyte to elicit antidepressant activity.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, the antidepressant fluoxetine protects cultured astrocytes from the deleterious effect of corticosterone through the induction of autophagic flux. Fluoxetine concretely increases mitophagy, which allows the elimination of damaged mitochondria and alleviates ROS production induced by corticosterone in astrocytes [83].…”
Section: Autophagy In Astrocytesmentioning
confidence: 99%
“…43,44 One finding supporting the role of antidepressants in autophagy was that fluoxetine (10 μM), a selective serotonin reuptake inhibitor (SSRI), could promote unblocked autophagic flux by enhancing the fusion of autophagosomes with lysosomes in primary astrocytes. 45 The tricyclic antidepressant amitriptyline was found to increase autophagy in primary neurons and astrocytes, similar to the selective serotonin reuptake inhibitor fluoxetine. A further expanded study found that amitriptyline and fluoxetine lead to the gradual accumulation of sphingomyelin in lysosomes, which stimulates autophagy via protein phosphatase 2A, ULK, Beclin, and LC3B.…”
Section: Discussionmentioning
confidence: 98%